Inhibition of Heat Shock Factor 1 Enhances Repressive Molecular Mechanisms on the POMC Promoter - Ciato, Denis; Li, Ran; Garcia, Jose Luis Monteserin; Papst, Lilia; D'Annunzio, Sarah; Hristov, Michael; Tichomirowa, Maria A.; Belaya, Zhanna; Rozhinskaya, Liudmila; Buchfelder, Michael; Theodoropoulou, Marily; Paez-Pereda, Marcelo; et al. (Neuroendocrinology, 2019)
Background: Cushing's disease (CD) is caused by adrenocorticotropic hormone (ACTH)-secreting pituitary tumours. They express high levels of heat shock protein 90 and heat shock factor 1 (HSF1) in comparison to the normal tissue counterpart, indicating activated cellular stress. Aims: Our objectives were: (1) to correlate HSF1 expression with clinical features and hormonal/radiological findings of CD, and (2) to investigate the effects of HSF1 inhibition as a target for CD treatment. Patients/Methods: We examined the expression of total and pSer326HSF1 (marker for its transcriptional activation) by Western blot on eight human CD tumours and compared to the HSF1 status of normal pituitary. We screened a cohort of 45 patients with CD for HSF1 by immunohistochemistry and correlated the HSF1 immunoreactivity score with the available clinical data. We evaluated the effects of HSF1 silencing with RNA interference and the HSF1 inhibitor KRIBB11 in AtT-20 cells and four primary cultures of human corticotroph tumours. Results: We show that HSF1 protein is highly expressed and transcriptionally active in CD tumours in comparison to normal pituitary. The immunoreactivity score for HSF1 did not correlate with the typical clinical features of the disease. HSF1 inhibition reduced proopiomelanocortin (Pomc) transcription in AtT-20 cells. The HSF1 inhibitor KRIBB11 suppressed ACTH synthesis from 75% of human CD tumours in primary cell culture. This inhibitory action on Pomc transcription was mediated by increased glucocorticoid receptor and suppressed Nurr77/Nurr1 and AP-1 transcriptional activities. Conclusions: These data show that HSF1 regulates POMC transcription. Pharmacological targeting of HSF1 may be a promising treatment option for the control of excess ACTH secretion in CD.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cushing's disease; Heat shock factor 1; KRIBB11; POMC